Adolescentent and Social Networkking: Do They Influence Policy Making? - Kusumasari, Bevaola (Kusumasari,Bevaola, 2013)
Citizen participation is simply understood as taking part In government decision-making process. The development of social networking affords a new way forthe youth to engage in policy formulatiomThis study highlights the way teenagers can use social media to legitimately participate in politics. The Survey comprised 120 teenagers drawn from the 13-19 age group In Yogyakarta, Indonesia. The survey entailed observation of teenagers' status on Facebook and TwitterStudy findings show that there has been a shift in the way teenagers participates in politic.%. Social networking has become major influence In teenagers' participation in politics owing to its due its practicality, flexibility and ability to enable them express their political and social concerns In personal ways. This finding highlights the importance of social networking as space which the government can use to engage teenagers' voice taw policy formulation. This article, examines contextual issues teenagers encounter in their lives, coupled with review of literature review on adolescents participation In politics, to determine whether social media is an effective policy-making tool in community political participation